Differential expression of serum miR-126, miR-141 and miR-21 as novel biomarkers for early detection of liver metastasis in colorectal cancer - Yin, Jie; Bai, Zhigang; Song, Jianning; Yang, Yun; Wang, Jin; Han, Wei; Zhang, Jun; Meng, Hua; Ma, Xuemei; Yang, Yao; Wang, Tingting; Li, Weirong; et al. (Chinese Journal of Cancer Research; Vol 26, No 1 (February 27, 2014): Chinese Journal of Cancer Research, 2014)
Objective: MicroRNAs (miRNAs) have potential as diagnostic biomarkers in cancer. Evaluation of the association between miRNA expression patterns and early detection of liver metastasis in colorectal cancer (CRC) has not been reported. Methods: We investigated the expression of metastasis-associated miRs-31, 335, 206, 141, 126, 200b, 200c, 21, Let7a, Let7b and Let7c in localized, liver-metastatic and other organ-metastatic CRC (OM-CRC). Expressions of target miRNAs in serum were evaluated in 116 consecutive localized CRC (L-CRC), 72 synchronous liver-metastatic CRC (SLM-CRC) and 36 other OM-CRC by quantitative real-time PCR. Results: Seven of 11 tested miRNAs could be detected from serum. Four miRNAs, miR-126, Let-7a, miR-141 and miR-21 were identified as metastasis-associated miRNAs. Compared with L-CRC, significant up-regulated expression was observed for miR-141 and miR-21 in SLM-CRC and OM-CRC, down-regulated expression was observed for miR-126 in SLM-CRC and OM-CRC, and up-regulated expression of Let-7a in OM-CRC. The receiver operating characteristic (ROC) curve showed serum miR-126 had a cut-off [log10 relative quantity (log10RQ)=–0.2005] with 77.78% sensitivity and 68.97% specificity with an area under curve (AUC) of 0.7564, miR-141 had a cut-off (log10RQ=–0.2285) with 86.11% sensitivity and 76.11% specificity with an AUC of 0.8279, and miR-21 had a cut-off (log10RQ=–0.1310) with 73.61% sensitivity and 66.38% specificity with an AUC of 0.7479. Conclusions: We identified liver metastasis-associated miRNAs, suggesting serum miR-126, miR-141 and miR-21 may be novel biomarkers for clinical diagnosis of early stage liver-metastatic CRC.